Weierstrass Elliptic and Modular Functions - 23.20 Mathematical Applications

From testwiki
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
23.20#Ex1 x 3 = m 2 - x 1 - x 2 subscript π‘₯ 3 superscript π‘š 2 subscript π‘₯ 1 subscript π‘₯ 2 {\displaystyle{\displaystyle x_{3}=m^{2}-x_{1}-x_{2}}}
x_{3} = m^{2}-x_{1}-x_{2}

x[3] = (m)^(2)- x[1]- x[2]
Subscript[x, 3] == (m)^(2)- Subscript[x, 1]- Subscript[x, 2]
Skipped - no semantic math Skipped - no semantic math - -
23.20#Ex2 y 3 = - m ⁒ ( x 3 - x 1 ) - y 1 subscript 𝑦 3 π‘š subscript π‘₯ 3 subscript π‘₯ 1 subscript 𝑦 1 {\displaystyle{\displaystyle y_{3}=-m(x_{3}-x_{1})-y_{1}}}
y_{3} = -m(x_{3}-x_{1})-y_{1}

y[3] = - m*(x[3]- x[1])- y[1]
Subscript[y, 3] == - m*(Subscript[x, 3]- Subscript[x, 1])- Subscript[y, 1]
Skipped - no semantic math Skipped - no semantic math - -
23.20.E5 v 8 ⁒ ( 1 + u 8 ) = 4 ⁒ u 4 superscript 𝑣 8 1 superscript 𝑒 8 4 superscript 𝑒 4 {\displaystyle{\displaystyle v^{8}(1+u^{8})=4u^{4}}}
v^{8}(1+u^{8}) = 4u^{4}
p = 2 𝑝 2 {\displaystyle{\displaystyle p=2}}
(v)^(8)*(1 + (u)^(8)) = 4*(u)^(4)
(v)^(8)*(1 + (u)^(8)) == 4*(u)^(4)
Skipped - no semantic math Skipped - no semantic math - -
23.20.E6 u 4 - v 4 + 2 ⁒ u ⁒ v ⁒ ( 1 - u 2 ⁒ v 2 ) = 0 superscript 𝑒 4 superscript 𝑣 4 2 𝑒 𝑣 1 superscript 𝑒 2 superscript 𝑣 2 0 {\displaystyle{\displaystyle u^{4}-v^{4}+2uv(1-u^{2}v^{2})=0}}
u^{4}-v^{4}+2uv(1-u^{2}v^{2}) = 0
p = 3 𝑝 3 {\displaystyle{\displaystyle p=3}}
(u)^(4)- (v)^(4)+ 2*u*v*(1 - (u)^(2)* (v)^(2)) = 0
(u)^(4)- (v)^(4)+ 2*u*v*(1 - (u)^(2)* (v)^(2)) == 0
Skipped - no semantic math Skipped - no semantic math - -
23.20.E7 u 6 - v 6 + 5 ⁒ u 2 ⁒ v 2 ⁒ ( u 2 - v 2 ) + 4 ⁒ u ⁒ v ⁒ ( 1 - u 4 ⁒ v 4 ) = 0 superscript 𝑒 6 superscript 𝑣 6 5 superscript 𝑒 2 superscript 𝑣 2 superscript 𝑒 2 superscript 𝑣 2 4 𝑒 𝑣 1 superscript 𝑒 4 superscript 𝑣 4 0 {\displaystyle{\displaystyle u^{6}-v^{6}+5u^{2}v^{2}(u^{2}-v^{2})+4uv(1-u^{4}v% ^{4})=0}}
u^{6}-v^{6}+5u^{2}v^{2}(u^{2}-v^{2})+4uv(1-u^{4}v^{4}) = 0
p = 5 𝑝 5 {\displaystyle{\displaystyle p=5}}
(u)^(6)- (v)^(6)+ 5*(u)^(2)* (v)^(2)*((u)^(2)- (v)^(2))+ 4*u*v*(1 - (u)^(4)* (v)^(4)) = 0
(u)^(6)- (v)^(6)+ 5*(u)^(2)* (v)^(2)*((u)^(2)- (v)^(2))+ 4*u*v*(1 - (u)^(4)* (v)^(4)) == 0
Skipped - no semantic math Skipped - no semantic math - -
23.20.E8 ( 1 - u 8 ) ⁒ ( 1 - v 8 ) = ( 1 - u ⁒ v ) 8 1 superscript 𝑒 8 1 superscript 𝑣 8 superscript 1 𝑒 𝑣 8 {\displaystyle{\displaystyle(1-u^{8})(1-v^{8})=(1-uv)^{8}}}
(1-u^{8})(1-v^{8}) = (1-uv)^{8}
p = 7 𝑝 7 {\displaystyle{\displaystyle p=7}}
(1 - (u)^(8))*(1 - (v)^(8)) = (1 - u*v)^(8)
(1 - (u)^(8))*(1 - (v)^(8)) == (1 - u*v)^(8)
Skipped - no semantic math Skipped - no semantic math - -